Mindful, Authentic, Strong Voice: Constructing A Mindfulness-Based Classroom Materials for EFL Poetry Learners - Piscayanti, Kadek Sonia (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2022)
Constructing mindfulness-based learning in the pandemic of covid-19 is a strategy to overcome the learning crisis especially in EFL poetry context. Online learning has replaced offline learning which makes a big shift in the learning process. The crisis happens due to the different mediums of teaching. Mindfulness is needed in this shift. Mindfulness takes place when crisis of learning happens, also for teachers in both designing and creating a proper material for the learners especially in EFL poetry classroom. This study attempts to investigate the construction of poetry learning materials in EFL context to enable the learners explore their truest self, the voice that they own but never shared. The previous research done on mindfulness rarely talked about the development of material in the EFL poetry context. This research tries to give new insight on how to develop an EFL poetry mindfulness-based learning material. The mindfulness-based learning and narrative inquiry are applied to gain the best understanding of what is needed by the students in the EFL poetry classroom. The data are gained from the mindfulness-based intervention, narrative inquiry-based instrument, and poetry scoring rubrics to identify the invention of the language identity. The findings revealed that the materials should stimulate the learners to be: open to new things, flexible to context, flexible to wider point of views, and create something new.